PEMETAAN PERILAKU OPPORTUNISTIK TERHADAP PROSPEK PERUSAHAAN MENDATANG MELALUI AKTIVITAS MANIPULASI - Muljanto Siladjaja; Markonah Markonah (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2019)
This research have tested out the influence of opportunistics’s behaviour on the fluctuation of market price  by using the manipulation activity later this research provide the mapping between investor’s decision with accruals quality in financial reporting. Because of  the usefullness information financial reporting, so that the investor can done the predicting the future prospect by estimating the growth rate, so it give the feedback to management. The dividend policy can be used s as the communication process, management have proclivity  to diseminate that the prospect had been better in the future. The previous research had tested out the using of accruals had been the negative perspective on investor’s view, so the research have developed out the estimation of discretionary accruals quality as an critical measurement of reducing the opportunistic behaviour. This research used the statistics model by developing the the multiple regresion by developing out  the new indicators for the estimated price, that based on earnings and equity as independent variables. This research have the causal approach by using the purposive sampling on the manufacturing industry by using the real based manipulation activity, so the manipulation activity had been treated as a proxy for grouping the patern of opportunistics behaviour. By using future market value based on earning and equity, the investor have enough capability in detecting the earning management, the investor have calculated the net market value in predicting the company’s prospect in future. In this research have developed out the accruals quality literature by mapping the feedback of interaction in decision tree model with Teorema Bayes. The positive perception of dividend policy show out the investor involvement in formulating cooperate operational policy. The investor’s positive perception can be formed when they found “the good” news by detecting out the negative manipulation and high accruals quality. It has paved the investor out the way in controlling and monitoring the company’s performance for the better prospect one. As novelty, this research have created out the new measurement in earning quality (by modifying a new formula for discretionary accruals quality) and future value market (based on earnings and equity). By re-shaping the new paradigms of the financial statement’ concept as decision usefulness information, this research have created out the predictive model in describing out the investor’s perception  and the asymmetric information area in efficient market.